2019
DOI: 10.1126/scitranslmed.aar6294
|View full text |Cite
|
Sign up to set email alerts
|

Targeting pancreatic islet PTP1B improves islet graft revascularization and transplant outcomes

Abstract: Deficient vascularization is a major driver of early islet graft loss and one of the primary reasons for the failure of islet transplantation as a viable treatment for type 1 diabetes. This study identifies the protein tyrosine phosphatase 1B (PTP1B) as a potential modulator of islet graft revascularization. We demonstrate that grafts of pancreatic islets lacking PTP1B exhibit increased revascularization, which is accompanied by improved graft survival and function, and recovery of normoglycemia and glucose to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 64 publications
(113 reference statements)
0
17
0
Order By: Relevance
“…Thus, our study indicates that selective inhibition of PTP1B is not only beneficial for glycaemic control but also conducive to the proliferation and viability of pancreatic beta cells. A more recent study confirmed that the protective effect exerted by PTP1B on islets represents another mechanism of action of the enzyme: targeting of pancreatic islet PTP1B improved islet graft revascularization and transplant outcomes (Figueiredo et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, our study indicates that selective inhibition of PTP1B is not only beneficial for glycaemic control but also conducive to the proliferation and viability of pancreatic beta cells. A more recent study confirmed that the protective effect exerted by PTP1B on islets represents another mechanism of action of the enzyme: targeting of pancreatic islet PTP1B improved islet graft revascularization and transplant outcomes (Figueiredo et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…Increased insulin sensitivity was observed in mice deficient of PTP1B [56,57]. In a mouse model of pancreatic islet transplantation into eye, deletion of PTP1B, elevated revascularization of the graft islet, increased graft survival, facilitated recovery of normoglycemia, and improved glucose tolerance [58]. These effects of loss of PTP1B were mediated via an increase in the expression of VEGF-A by β cells, following activation of the peroxisome proliferator-activated receptor γ coactivator 1α (PGC1α) and the estrogen-related receptor α [58].…”
Section: Reversible Inhibition Of Protein Tyrosine Phosphatase 1b (Ptp1b) By Rosmentioning
confidence: 99%
“…To assess vascularization and cell viability in ACE implants, iβ-like clusters were labeled with the long-term tracer for viable cells CFDA (Invitrogen) before transplantation. At day 10 post-transplantation, mice received an intravenous injection of RITC-dextran and in vivo imaging was used to assess functional vascularization and cell viability 34 . For determination of glucose-induced insulin secretion, mice were fasted for 5-6 h and then injected intraperitoneally with glucose (3g/Kg).…”
Section: Graft Viability and Function Analysismentioning
confidence: 99%